Child-to-Adult Liver Transplantation With Donation After Cardiac Death Donors: Three Case Reports. Issue 7 (February 2016) - Hu, Liangshuo; Liu, Xuemin; Zhang, Xiaogang; Yu, Liang; Sha, Huanchen; Zhou, Ying; Tian, Min; Shi, Jianhua; Wang, Wanli; Liu, Chang; Guo, Kun; Lv, Yi; et al.
Abstract : Abstract: Development of organ transplantation is restricted by the discrepancy between the lack of donors and increasing number of patients. The outcome of pediatric donors transplanted into adult recipients especially with donation after circulatory death (DCD) pattern has not been well studied. The aim of this paper is to describe our experience of 3 successful DCD donor child-to-adult liver transplantations lately. Three DCD donors were separately 7, 5, and 8 years old. The ratio between donor graft weight and recipient body weight was 1.42%, 1.00%, and 1.33%, respectively. Ratio between the volume of donor liver and the expected liver volume was 0.65, 0.46, and 0.60. Splenectomy was undertaken for the second recipient according to the portal vein pressure (PVP) which was observed during the operation. Two out of 3 of the recipients suffered with acute kidney injury and got recovered after renal replacement therapy. The first recipient also went through early allograft dysfunction and upper gastrointestinal bleeding. The hospital course of the third recipient was uneventful. After 1 year of follow-up visit, the first and second recipients maintain good quality of life and liver function. The third patient was followed up for 5 months until now and recovered well. DCD child-to-adult liver transplantation should only be used for comparatively matched donor and recipient. PVP should be monitored during the operation. The short-term efficacy is good, but long-term follow-up and clinical study with large sample evaluation are still needed.